MicroRNA-124: A Key Player in Microglia-Mediated Inflammation in Neurological Diseases - Zhao, Jiuhan; He, Zhenwei; Wang, Jialu (Frontiers in Cellular Neuroscience, 2021)
Neurological disorders are mainly characterized by progressive neuron loss and neurological deterioration, which cause human disability and death. However, many types of neurological disorders have similar pathological mechanisms, including the neuroinflammatory response. Various microRNAs (miRs), such as miR-21, miR-124, miR-146a, and miR-132 were recently shown to affect a broad spectrum of biological functions in the central nervous system (CNS). Microglia are innate immune cells with important roles in the physiological and pathological activities of the CNS. Recently, abnormal expression of miR-124 was shown to be associated with the occurrence and development of various diseases in CNS via regulating microglia function. In addition, miR-124 is a promising biomarker and therapeutic target. Studies on the role of miR-124 in regulating microglia function involved in pathogenesis of neurological disorders at different stages will provide new ideas for the use of miR-124 as a therapeutic target for different CNS diseases.